CURRENT STATE OF INTERNAL AUDIT ORGANIZATION IN COMMERCIAL BANKS AND THE KEY CHALLENGES AFFECTING ITS EFFECTIVENESS (International Congress on Economics, Management and Business Studies, 2026)
This thesis analyzes the current state of the organization and implementation of internal audit processes in commercial banks of Uzbekistan. Six major groups of factors reducing the effectiveness of internal audit activities are systematized, and their cause-and-effect relationships are identified and explained.
Keywords: internal audit service, audit plan, human resource capacity, recommendation monitoring, audit effectiveness, digitalization, independence.